Critical Thinking Skills of Students Through Guided Discovery Learning Model Assisted by PhET Media on Stationary and Walking Wave - Azhar; Rizki Ezra Manik; Rafika Nabila; Daeng Ayub Natuna; Dedi Irawan (Postgraduate, University of Mataram, 2024)
The research aims to describe students' thinking skills in the guided discovery learning model assisted by PhET media. The design used is a quasi- experimental: Posttest only control group design. The population in this study were all students of class XI SMA Negeri 2 Koto Kampar Hulu Academic Year 2021/2022 with a sample of 52 students consisting of class XI MIPA 1 as an experimental class totaling 28 students and class XI MIPA 2 as a control class. totaling 24 students. The data collection instrument was a test of critical thinking skills on stationary and running wave material consisting of 10 multiple choice questions. The data analysis technique used is descriptive analysis through the average value of students critical thinking skills and inferential analysis through the normality test, homogeneity test, and hypothesis testing with the help of the SPSS 25 program. The results showed that learning became more effective as seen from the average score - the average thinking skills of students in the experimental class were better than the control class and there were significant differences in students' critical thinking skills between the experimental class that applied the PhET media-assisted guided discovery learning model and the control class.